Mini‐Review: Comprehensive Drug Disposition Knowledge Generated in the Modern Human Radiolabeled ADME Study. (31st July 2020) - Spracklin, Douglas K.; Chen, Danny; Bergman, Arthur J.; Callegari, Ernesto; Obach, R. Scott
Abstract : The human radiolabeled absorption, distribution, metabolism, and excretion (ADME) study offers a quantitative and comprehensive overall picture of the disposition of a drug, including excretion pattern and metabolite profiles in circulation and excreta. The data gathered from the ADME study are highly informative for developing a cohesive strategy for clinical pharmacology studies. Elements of standard ADME study designs are described. An exciting new development in human ADME studies is the application of accelerator mass spectrometry (AMS) as the detection technique for carbon‐14, in replacement of radioactivity measurements. This technology permits administration of 100‐fold to 1, 000‐fold lower amounts of carbon‐14, and thus opens the door to the application of new study designs. A new ADME study design, termed the AMS‐Enabled Human ADME study, is described. In this design, both oral and intravenous administration are assessed in a single clinical study with a two‐period crossover. In addition to all of the standard ADME study end points (e.g., mass balance and quantitative metabolite profiles), the AMS‐Enabled ADME study can provide the fundamental pharmacokinetic parameters of clearance, volume of distribution, absolute oral bioavailability, and even estimates of the fraction of the dose absorbed. Thus, we have entered a new era of human ADME study design that can yield vastly more informative and complete data sets enabling a superior understanding of overall drug disposition.